Wireless Sensor Network: Smart greenhouse prototype with smart design - Ismail M.T.; Ismail M.N.; Sameon S.S.; Zin Z.M.; Mohd N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cost engineering; Digital devices; Digital radio; Greenhouses; Humidity control; Multi agent systems; Robotics; Wireless telecommunication systems; Zigbee; Protoype; Radiofrequency technology; Research and development; Temperature and humidities; Wired and wireless; Wireless sensor; Wireless sensor technology; ZigBee technology; Wireless sensor networks